2022
DOI: 10.1029/2022gc010619
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Strategy From S‐Wave Receiver Functions Reveals Distinct Lateral Variations of Lithospheric Thickness in Southeastern Tibet

Abstract: The lithosphere-asthenosphere boundary (LAB) is generally considered to be a negative velocity gradient (NVG) transition zone from the cold and fast lithosphere to the warm and slow asthenosphere. Its depth varies considerably, ranging from ∼0 km in mid-oceanic ridge, to <50 km beneath the young oceans, and then to >200 km beneath cratonic regions (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…In this case, both the retreat of the Indian slab and lithospheric delamination of the western Yangtze might cause asthenosphere upwelling between the EHS and western Yangtze, which might be observed as the mushroomshaped LVZ. The asthenosphere upwelling and lithospheric delamination could explain the lateral variation of the LAB depth (Zhang et al, 2010;Zhang and Deng, 2022), the localized crust-mantle low velocity and weak azimuthal anisotropy (Bao et al, 2020) as well as the depressed 660-km discontinuity observed beneath the eastern margin of the Tibetan Plateau (Figure 6). Consequently, convergence between the eastern Tibetan Plateau and western Yangtze Craton would be accommodated in the upper crust dominantly by pure-shear thickening above the zone of mantle upwelling, and the crustal deformation will be characterized by contraction at the plateau margins and extension within the plateau (Gray and Pysklywec, 2012).…”
Section: Lithospheric Delamination and Asthenosphere Upwelling Beneat...mentioning
confidence: 99%
“…In this case, both the retreat of the Indian slab and lithospheric delamination of the western Yangtze might cause asthenosphere upwelling between the EHS and western Yangtze, which might be observed as the mushroomshaped LVZ. The asthenosphere upwelling and lithospheric delamination could explain the lateral variation of the LAB depth (Zhang et al, 2010;Zhang and Deng, 2022), the localized crust-mantle low velocity and weak azimuthal anisotropy (Bao et al, 2020) as well as the depressed 660-km discontinuity observed beneath the eastern margin of the Tibetan Plateau (Figure 6). Consequently, convergence between the eastern Tibetan Plateau and western Yangtze Craton would be accommodated in the upper crust dominantly by pure-shear thickening above the zone of mantle upwelling, and the crustal deformation will be characterized by contraction at the plateau margins and extension within the plateau (Gray and Pysklywec, 2012).…”
Section: Lithospheric Delamination and Asthenosphere Upwelling Beneat...mentioning
confidence: 99%
“…Since the deployment of seismic arrays by international collaborative projects such as PASS-CAL, INDEPTH, and HiCLIMB during the last few decades, many investigations have been conducted to obtain further insight into the evolution processes and small-scale deep structures of the Himalayan-Tibetan orogen [27][28][29][30][31][32][33]. In addition, much seismological research has been conducted in the Tibetan Plateau over the past decade, such as deep seismic soundings [34][35][36][37], seismic tomography [38][39][40][41][42][43][44][45][46], and teleseismic receiver functions [47][48][49][50][51]. However, most of the previous studies paid much more attention to southeastern Tibet and there are few studies on the detailed 3D velocity structure of the upper mantle beneath the YTS due to the limitations of the available seismic data.…”
Section: Introductionmentioning
confidence: 99%